Hepatitis B (HB) immunoglobulin plus HB vaccine for intrauterine HB virus infection. Issue 3 (22nd January 2015) - Iwasawa, Kentaro; Inui, Ayano; Tsunoda, Tomoyuki; Kondo, Takeo; Kawamoto, Manari; Sogo, Tsuyoshi; Komatsu, Haruki; Fujisawa, Tomoo
Abstract Background Vaccination against hepatitis B virus (HBV) infection in infants born to hepatitis B surface antigen (HBsAg)‐positive mothers using HB immunoglobulin (HBIG) and hepatitis B (HB) vaccine was launched in Japan in 1985. Infants testing positive for HBsAg at 1 month of age are considered to have prenatally acquired the infection and are usually excluded from the prevention program. Infants born to HB e antigen (HBeAg)‐positive mothers are at a high risk of perinatally acquiring the infection. In this study, long‐term outcome was evaluated in children with prenatal HBV infection who received the HBIG and HB vaccine in Japan. Methods Newborns of both HBsAg‐ and HBeAg‐positive carrier mothers received HBIG within 48 h of birth and at 2 months of age. Subsequently, three doses of recombinant HB vaccine were given at 2, 3, and 5 months of age. Outcome was compared between the following two groups: infants who completed the vaccination program, even if they were HBsAg positive at 1 month of age (n = 15), and infants who did not (n = 51). Results Seroconversion from HBeAg to anti‐HBe antibody (HBeAb) before 3 years of age was observed in five children (33%) who completed the vaccination program and in two (4%) who did not (P = 0.005). In 2/5 children who completed the vaccination program and achieved HBeAb seroconversion, seroconversion from HBsAg to anti‐HBs antibody was also noted. Conclusion This specific vaccination program for children with prenatal HBV infection has the potential to alter immune tolerance to HBV.